Oral Human Papillomavirus Infection and Head and Neck Squamous Cell Carcinoma in Rural Northwest Cameroon. Issue 1 (January 2019) - Rettig, Eleni M.; Gooi, Zhen; Bardin, Richard; Bogale, Mesele; Rooper, Lisa; Acha, Everistus; Koch, Wayne M.
Objective: Oral human papillomavirus (HPV) infection is the precursor for a growing subset of oropharyngeal squamous cell carcinomas (OPSCCs) in the developed world. This study was designed to characterize oral HPV infection and OPSCC in a region with high rates of HPV-driven cervical cancer. Study Design: Cross-sectional cohort study, retrospective case series. Setting: Northwest Cameroon referral hospital. Subjects and Methods: Individuals infected with human immunodeficiency virus attending an outpatient clinic were evaluated for oral HPV infection with oral swabs or rinses that were tested for 51 HPV types. HNSCCs diagnosed and/or treated at the same hospital from 2011 to 2017 were retrospectively reviewed to ascertain demographic and tumor characteristics, and available OPSCCs were tested for HPV. Results: The oral HPV infection study population comprised 101 participants. Most (69%) were female and never-smokers (84%). Participants had median 4 lifetime sexual partners (interquartile range, 3-7; range, 1-100). Five participants (5%) had oral HPV infection; one had 2 HPV types. HPV types detected were HPV68 (n = 2), HPV82 (n = 2), HPV32 (n = 1), and unknown (n = 1). No significant demographic or behavioral differences were detected among individuals with vs without oral HPV infection. OPSCCs comprised just 8% (n = 11) of 131 HNSCCs in the retrospective study population. Two of 7 OPSCCs were HPV positive. Conclusion: The low prevalence of OPSCC observed in northwest Cameroon together with the rarity of oral HPV infection suggests low rates of HPV-driven oropharyngeal carcinogenesis in the region. Future research should examine how geographic differences in oral HPV infection are influenced by cultural norms and affect HPV-OPSCC epidemiology.